ANALISIS EFISIENSI PENGGUNAAN MODAL KERJA KOPERASI SERBA USAHA CAHAYA MUTIS KEFAMENANU - Duli, Dominikus Kopong; Ximenes, Sonya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2021)
Cooperatives are one of the lifeblood of the nation's economy and need to be managed properly so that they can increase the welfare of members. Capital in the form of principal savings and mandatory savings and loan capital and external donations needs to be managed effectively and efficiently. Funds collected and spent in capital work, continue to be monitored and controlled so that cooperative activities continue to run according to plan. The efficiency of using working capital is analyzed and evaluated in order to obtain information about its management performance. The results of the analysis show that the efficiency of the use of working capital from a liquidity point of view is not good. Meanwhile, from the activity point of view, it also shows an inefficient state. It is hoped that there will be a management policy not to accumulate fresh funds that do not provide benefits. Continue to provide better loan services for members and schedule receivables receivables so that the receivables turnover frequency can be higher. The higher the receivables turnover, the better the financial performance of the cooperative.